The tilting house - Llewellyn, Tom (Thomas Richard), 1964- (Tricycle Press, 2010)
When Josh, his parents, grandfather, and eight-year-old brother move into the old Tilton House, they discover such strange things as talking rats, a dimmer switch that makes the house invisible, and a powder that makes objects grow.